1986
DOI: 10.1063/1.337167
|View full text |Cite
|
Sign up to set email alerts
|

Polymer dispersed nematic liquid crystal for large area displays and light valves

Abstract: A new electro-optical material based on nematic liquid crystal dispersed in a polymer matrix has recently been introduced by Fergason. This technology (termed NCAP, for nematic curvilinear aligned phase) is suitable for making very large area (thousands of square centimeter) light valves and displays. The device consists of micron size droplets of liquid crystal dispersed in and surrounded by a polymer film. Light passing through the film in the absence of an applied field is strongly forward scattered, giving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
217
1
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 540 publications
(222 citation statements)
references
References 9 publications
1
217
1
3
Order By: Relevance
“…In particular, the alignment of the dipole moment of the dye with the director of the LC offers the prospect of a coloured liquid crystal display (LCD) that can be switched to a transparent state in an on-off fashion with an external electric field [1][2][3][4]. Additionally, it has been observed that the electro-optic response time of nematic LCs can be improved by dye dopants with large dipole moments, which is also of great interest in display applications [5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the alignment of the dipole moment of the dye with the director of the LC offers the prospect of a coloured liquid crystal display (LCD) that can be switched to a transparent state in an on-off fashion with an external electric field [1][2][3][4]. Additionally, it has been observed that the electro-optic response time of nematic LCs can be improved by dye dopants with large dipole moments, which is also of great interest in display applications [5].…”
Section: Introductionmentioning
confidence: 99%
“…The liquid crystal displays (LCDs) with light scattering properties using nematic liquid crystals and polymers have been studied [1][2][3][4][5]. Polymer Network (PN) LCD, which contains a dispersed three dimensional polymer network in liquid crystal (PNLC), is one of the most promising light scattering displays because of the compatibility of brightness and low driving voltage.…”
Section: Introductionmentioning
confidence: 99%
“…A major disadvantage of the smart glass, the need for a voltage source, can be resolved by the integration of photovoltaic (PV) devices [12], [13], which means lower power consumption is desirable. PDLCD [14], one type of smart glass, is often used to realize electrically controlled privacy glass thanks to its scattering property [15]. PDLCDs generally scatter light when they are OFF and transparent when ON, and a reverse mode PDLCD works as expected [16].…”
Section: Copyright Cmentioning
confidence: 99%